Sleep disorders, cardiovascular symptoms and body weight dynamics in women with post-COVID-19 syndrome - V. A. Sergeeva; T. E. Lipatova (Медицинский совет, 2022)
Introduction. The COVID-19 pandemic has become a global health problem worldwide. The consequences of the new coronavirus infection continue to be studied. Cardiovascular symptoms and sleep disorders are among the dominant complaints in postCOVID-19 syndrome in women.Aim. To assess sleep disorders, cardiovascular symptoms, body weight dynamics and their statistical relationships in women with post-COVID-19 syndrome.Materials and methods. Using a voluntary anonymous questionnaire, we assessed cardiovascular symptoms, body weight dynamics and sleep disorders in 253 women of different age groups who had COVID-19 at least 12 weeks ago. The severity of dyspnea was assessed using the mMRC (Modified Medical Research Council) scale. Resting heart rate was measured. Statistical processing of the obtained data was carried out using the StatPlus 2009 Professional program.Results and discussion. Among the manifestations of the cardiovascular system in post-COVID-19 syndrome in women of different age groups, palpitations, shortness of breath, and increased blood pressure predominate. There is a statistical pattern in the increased prevalence of rises in blood pressure in post-COVID-19 syndrome among women, depending on age. A variety of sleep disorders occur in all age groups of women, most often in the group of older women. Statistical relationships between sleep disorders and increased blood pressure, severity of dyspnea, palpitations in post-COVID-19 syndrome in women of different age groups were revealed. Severe dyspnea in post-COVID-19 syndrome was frequent noticed in older women. Weight loss in women with post-COVID-19 syndrome is associated with sleep disorders.Conclusions. Cardiovascular symptoms and sleep disorders in post-COVID-19 syndrome in women of different age groups are closely interrelated. The management of patients in post-COVID-19 syndrome should be carried out taking into account the diversity and interaction of various clinical manifestations. Correction of the identified violations should be comprehensive, based on an interdisciplinary approach of various specialists.